Visual outcomes with a non-diffractive enhanced depth-of-focus IOL in patients with age-related macular degeneration - Elvira, Juan Carlos; Devesa, Patricia; Elvira-Giner, Belén; Tañá-Sanz, Pedro; Orts-Vila, Paz; Tañá-Rivero, Pedro (Frontiers in Medicine, 2025)
PurposeTo evaluate visual function in eyes with age-related macular degeneration (AMD) implanted with a non-diffractive enhanced depth-of-focus (EDOF) intraocular lens (IOL) after cataract surgery.DesignProspective, observational, non-randomized clinical study.MethodsTwenty-two eyes from 22 patients diagnosed with AMD and cataracts were submitted to standard cataract surgery with a non-diffractive EDOF IOL implantation (AcrySof IQ Vivity). We measured monocular uncorrected and best-corrected-distance visual acuity (UDVA and CDVA), uncorrected- and distance-corrected-intermediate visual acuity (UIVA and DCIVA), uncorrected- and distance-corrected-near visual acuity (UNVA and DCNVA), manifest refractive spherical equivalent (MRSE) and cylinder, monocular defocus curve and patient-reported outcome questionnaires (Catquest-9SF and NEI VFQ-25). Follow-up visits were carried out at 1, 3 and 6 months post-surgery.ResultsAt 6 months post-surgery all eyes were within ± 0.50 D with a mean MRSE of −0.19 ± 0.20 D, 95.45% had a refractive cylinder of ≤ 0.50 D with a mean cylinder of −0.24 ± 0.27 D. The mean values of postoperative monocular CDVA, DCIVA, and DCNVA were 0.02 ± 0.08, 0.16 ± 0.11, and 0.26 ± 0.15 logMAR, respectively. The defocus curve showed good visual acuity at distance and intermediate with a depth-of-focus of about 1.60 D. A total of 81.82% of patients did not report any difficulty with their vision in their everyday-life and 86.36% reported being quite satisfied to very satisfied with their current vision. The NEI VFQ-25 showed that all values improved significantly (p < 0.05) after the surgery in the different parameters analyzed except for ocular pain (p = 0.390) and color vision (p = 0.333).ConclusionThe use of a non-diffractive EDOF IOL in AMD eyes with cataracts is a safe and effective surgical approach for visually correcting aphakia, providing good visual acuity at far and intermediate distances. Our outcomes support the use of non-diffractive EDOF IOLs in patients with AMD diagnosed with cataracts aiming to obtain spectacle-independence at far and intermediate distances.